Pattern and clinical predictors of lymph node metastases in epithelial ovarian cancer. Issue 6 (1st October 2007) - Harter, P.; Gnauert, K.; Hils, R.; Lehmann, T. G.; Fisseler-Eckhoff, A.; Traut, A.; Du Bois, A.
Abstract : Para-aortic lymphadenectomy is part of staging in early epithelial ovarian cancer (EOC) and could be part of therapy in advanced EOC. However, only a minority of patients receive therapy according to guidelines or have attendance to a specialized unit. We analyzed pattern of lymphatic spread of EOC and evaluated if clinical factors and intraoperative findings reliably could predict lymph node involvement, in order to evaluate if patients could be identified in whom lymphadenectomy could be omitted and who should not be referred to a center with capacity of performing extensive gynecological operations. Retrospective analysis was carried out of all patients with EOC who had systematic pelvic and para-aortic lymphadenectomy during primary cytoreductive surgery. One hundred ninety-five patients underwent systematic pelvic and para-aortic lymphadenectomy. Histologic lymph node metastases were found in 53%. The highest frequency was found in the upper left para-aortic region (32% of all patients) and between vena cava inferior and abdominal aorta (36%). Neither intraoperative clinical diagnosis nor frozen section of pelvic nodes could reliably predict para-aortic lymph node metastasis. The pathologic diagnosis of the pelvic nodes, if used as diagnostic tool for para-aortic lymph nodes, showed a sensitivity of only 50% in ovarian cancer confined to the pelvis and 73% in more advanced disease. We could not detect any intraoperative tool that could reliably predict pathologic status of para-aortic lymph nodes. Systematic pelvic and para-aortic lymphadenectomy remains part of staging in EOC. Patients with EOC should be offered the opportunity to receive state-of-the-art treatment including surgery